Preparation of benzoyl fluorides and benzoic acids from phenols via a dearomatization–rearomatization strategy. Issue 8 (13th March 2023) - Yang, Meixian; Huang, Xinyue; Miao, Wenjun; Yi, Lan; Cai, Jiajing; Zhao, Zhenghuan; He, Jia; Qiu, Dachuan
Abstract : We describe here a method to generate both benzoyl fluorides and benzoic acids using 2, 5-cyclohexadienones prepared from phenols. Abstract : We describe here a method to generate both benzoyl fluorides and benzoic acids using 2, 5-cyclohexadienones prepared from phenols via oxidative dearomatization. 2, 5-Cyclohexadienones react with difluoromethyl 2-pyridyl sulfone under basic conditions to give gem -difluoroolefins in situ, which could be attacked by nucleophiles and further aromatized to form benzoyl fluorides. By changing the reaction conditions, benzoic acids could be formed efficiently in a one-pot fashion as well. The mild conditions and broad substrate scope make this transformation a unique approach for formal deoxyacylation of phenols without transition metal catalysis.